A Comparison between the Effects of Nasal Lavage with Hypertonic, Isotonic and Hypotonic Saline Solutions for the Treatment of Chronic Sinusitis - Nader Saki (Journal of Global Pharma Technology, 2017)
Background and Objectives Nasal lavage is an adjuvant treatment used for sinonasal diseases like sinusitis. There is no general consensus on the superiority of one of the three common solutions of hypertonic saline, hypotonic saline, and isotonic saline for the treatment of sinusitis’s symptoms. Furthermore, the majority of past studies have focused on two solutions of isotonic saline and hypertonic saline. In addition, no study has been published on the effect of hypotonic saline in the treatment of sinusitis symptoms. More importantly, in Iran no study has been conducted on this area. Due to the high importance of sinusitis disease and spending a lot every year for the treatment of the disease and its complications arising from it for patients and the country’s health system and with regard to the auxiliary use of saline solution is an inexpensive and easy treatment, we decided to conduct this study. Methods & Materials: This clinical trial study was conducted on 185 patients with chronic sinusitis referred to Imam and Apadana Hospitals (Ahvaz, Iran). With a diagnosis of chronic sinusitis by an ear, nose and throat specialist and using the CT scan, the patients have been selected. For collecting the data the necessary symptoms and information on the patients were recorded in a standard information gathering questionnaire. The patients were randomly divided into four groups. The first group received medication the second group medication as well as nasal lavage or hypertonic saline; the third group received medication in addition to nasal lavage or isotonic saline; the fourth group received medication plus nasal lavage or hypotonic saline. Results The results show the nasal lavage has an optimal therapeutic effect on headache symptoms, discharge from the nose and throat, coughing, nasal obstruction, olfactory problems, feeling of fullness in the face and according to all the criteria the isotonic saline has a useful treatment effect and is more effective than the hypertonic saline and has improved the nasal obstruction in about 50% of patients. Conclusion our findings showed better therapeutic features for isotonic saline solution with no serious side effects compared with the use of this solution is of greater priority.Keywords: Nasal lavage, Chronic Sinusitis, Isotonic, Hypotonic, Hypertonic Saline.